STUDI POTENSI ATRAKSI WISATA DALAM PENGEMBANGAN PARIWISATA ALAM DI TAMAN NASIONAL KOMODO DAN SEKITARNYA (Studi Kasus di Pantai Pede dan Desa Komodo, Kabupaten Manggarai Barat) - , KORNELIA WEBLIANA B ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Labuan Bajo and Komodo National Park is an united natural tourism destination. The increase of the number of the visiting in Komodo National Park (TNK) is expected to have a positive impact on the development of natural tourism in Labuan Bajo. This research is aimed at knowing : 1) what and how the potency of tourism attraction in Labuan Bajo area and Komodo island, 2) the perception and the motivation of the tourists visiting Labuan Bajo and Komodo island, 3) the perception and the participation of people toward the management of Pede beach tourism in Labuan Bajo and the development of tourism village in Komodo. The method of this research was descriptive and the sample collection used purpose sampling. The evaluation of the attractive potency was done by direct evaluation toward object. From the evaluation, the result showed that the value of Pede Beach deserved to be developed. The tourism attraction object was 70,24%, area condition was 84,44%, the infrastructure was 76,11%, the accessibility was 100%. The potency of Pink Beach (Pantai Merah) which deserved to be developed were object attraction tourism (95,71%), sea potency (78,67%), area condition (76, 67%) while the potency which did not deserve to be developed were the infrastructure (33,33%) and the accessibility (43,30%). Generally, Pink Beach (Pantai Merah) was almost feasible to be developed (65,66%), but the quantitative calculation on Pink Beach is in the category of not yet feasible to be developed (33,3%-66,6%). The result of questionnaire on visiting motivation showed that 72,22% of tourist had a motivation for recreaction, 7,78% of tourist had a motivation for research, 14, 44% of tourist had a motivation for education. The percentage of tourists who were satisfied visiting Labuan Bajo was 90% while 10% were not. The percentage of tourists expressed the intention for a returning visit was 63% while 37% others say they did not. Labuan Bajoâs people had a low participation in planning and managing beach area. The participation of people in forming Komodo Village had a low participation (42,35%) the level of peopleâs knowledge about Komodo national Park seemed to be in medium level (62,25%), the peopleâs response toward the existence of tourism village, in terme of an oppurtunity to increase their economic condition were medium (47,06%)